Seed-borne Infection and Development of Colletotrichum capsici in Naturally Infected Chili Seed - Wan Nik, Wan Zainun; Meon, Sariah (1988)
The testing of seeds using both the blotter and potato dextrose agar showed infection of Colletotrichum capsici to be well established both within and on the external surfaces of chilli seeds. Microtome sections showed that mycelia were present in the outer and inner layers of the testa and in the endosperm region. Formation of the acervulus was initiated below the seed coat and also in the endosperm and emerged to the surface after disrupting the seed coat. Parenchymatous tissues were also distorted. The pathogen finally grows on the seed surface.